A cowboy under my Christmas tree - Dailey, Janet (New York : Kensington Publishing Corp., 2012)
Sam Bennett is in Manhattan for the Christmas season, setting up Christmas trees all over the city, when he meets beautiful Nicole Young and a small boy with a big wish. Will they all get what they really want for Christmas?
"Kensington Books"
Keywords: Ranchers -- Fiction; Window dressers -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Manhattan (New York, N.Y.) -- Fiction; Love stories; Love stories